Improving Students’ of Senior High School Writing Ability through Cue Card in Short Story : English - Petrus Jacob Pattiasina; Aditya Ridho Fatmawan; Trimey Liria Hutauruk; Zulkifli Tanipu; Agus Rofi'i; Agnes Tesalonika Yolanda (Prodi Tadris Bahasa Inggris, 2023)
The author uses the cue card application method in the learning process. This study aims todetermine the level of students' writing ability through the use of cue cards in Senior HighSchool. The method of this research is classroom action research. The data collectiontechniques used were interview, observation, and writing test. The teacher observation sheetwas used to assess how the teacher used cue cards in the classroom, the student activityobservation sheet, and the student work test questions were used to evaluate and determine thecreativity of X grade students of SMA Negeri 1 Maluku. The results of the meeting stated thatthe success of cycle I research had not been achieved because those who scored ≥ 70 were 24students. In cycle II, 36 students scored more than ≥70. This means that the target of learninghas been achieved. This can be seen from the students' score of 60% from cycle I to 90% incycle II. Based on these results, it can be concluded that the application of cue cards has apositive impact on students' writing skills, this can be seen from the increasing writing skills oftenth grade students at SMA Negeri Maluku.